Sacred spaces: rock paintings of the Komati-LiGwa study area, Mpumalanga - Maseko, Mduduzi (My University, 2021)
This dissertation identifies 27 painted sites in central Mpumalanga Province, in areas adjacent to the Komati and LiGwa (Vaal) Rivers. It finds that the locations of the painted sites overlap with the social landscape of historically and ethnographically recorded BaTwa (San/Bushmen) in this region, particularly the Tlou-tle (//Xegwi), whose descendants were studied by linguists and anthropologists in the early and mid-1900s. The dissertation also identifies patterns between site placement and places in the landscape that the Tlou-tle attached ritual importance to, and finds that the placement of diverse images in the same spaces, and the continued use of sites by temporally separated painters, shows ideological similarities and continuities in the conception of space. Engagement between diverse rock arts in the Komati-LiGwa Study Area (KLSA) shows that the ritual landscape was characterised by different ‘ways of doing’; the extent to which interactions happened between painters of diverse origins cannot be discerned, but the art shows that worldviews met and blended. At some sites, ‘geometric’ paintings take on the technique of fine-line painting and also appear to ‘interact with the rock face’—both aspects predominantly associated with foragers. Figurative paintings are also executed in the finger technique at some sites and, later (as is indicated by the subject matter), a combination of finger and rough-brush techniques is used. Two factors are proposed to explain the variability of the art and its co-occurrence at sites—similarities in the conception of ‘place’ and the common experience of colonialism. With regards to the latter, historical records show that indigenous peoples in this region were subjected to farm labour since the middle of the nineteenth century, and hence previously independent communities possibly blended on colonial farms, and created new communities. Indeed, some of the rock art shows that it was painted in the colonial period, and from the symbols, and painting technique used for this art, we can see that changes in the art were consistent with changes and increasing complexity in the social landscape. These changes were brought, it is argued, also through responses to contact with multiple waves of ‘newcomers’, including the painters of ‘geometric’ art, all of whom contributed to the collective identity of ‘BaTwa’ in this region
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in in Archaeology to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021